Menelusuri Konvergensi Pedagogi Montessori dan STEAM: Dari Fondasi Sensorial hingga Scientific Inquiry dalam Pendidikan Anak Usia Dini (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This literature review explores the intersection of Montessori pedagogy, which emphasizes sensorial learning, and STEAM (Science, Technology, Engineering, Arts, and Mathematics), which highlights scientific inquiry in early childhood education. Montessori education prioritizes sensorial exploration, hands-on activities, observation, structured experiences, and interdisciplinary learning, all of which nurture children’s natural curiosity. Similarly, STEAM education encourages experimentation, problem-solving, creativity, innovation, and critical thinking through integrated approaches. Both approaches share a commitment to experiential and inquiry-based learning, supporting holistic child development. In early childhood, STEAM is often introduced through activities grounded in children’s daily observations and experiences, an approach that resonates strongly with Montessori principles. However, much of the research on STEAM in early education has focused primarily on cognitive and technological dimensions, often overlooking classical educational philosophies. This review seeks to bridge that gap by highlighting how Montessori’s sensorial foundation can serve as an essential entry point for scientific inquiry in early learning. Drawing from literature published since 2020, along with books and relevant sources, this review identifies key principles and areas of convergence between Montessori and STEAM. Beyond theoretical contributions, it also provides practical implications for educators, suggesting that Montessori environments can strengthen STEAM-based learning while inspiring further empirical research.